The Images, Figures and Plots in the Parables of Jesus and their Background in the Old Testament - Sheil, Arthur John (My University, 1967)
The thesis attempts to establish a link between the Parables of Jesus and that portion of Jewish Sacred literature that is included in the Old Testament in the area of images, figures and plots presented in the parables. As such it includes a definition of parable and allegory as well as a review of the principle way in which the details in the parables have been interpreted at selected points in history.
Keywords: Religion; Religion